Consumers’ perception of edible flowers using free word association (Research, Society and Development, 2021)
Edible flowers are trend in the novel food sector since they may be inserted in natural, health and eco-innovation approach. However, there is little information in literature about consumers perception about them, mainly in western society. Thus, the objective of the present work is to evaluate Brazilians perception about roses, hibiscus, ipê and pansy as edible flowers. An online survey was applied using a free word association methodology and a check-all-that-apply for their application in gastronomy. Results from word association show that all flowers were highly associated to positive attitudes and feelings, appearance and application aspects. Environmental words were also highlighted within the responses. These features were significantly related to frequency of buying new foods and show up as important characteristics to be explored for enhance edible flowers popularity. For application of them within food formulations, rose and hibiscus were tracked to tea, jam, bread and cookies utilization, meanwhile pansy to salads. Ipê was not related to none of gastronomy applications. Results indicate that knowledge of tangible and intangible flowers features, such as functional, environmental and application aspects can change and enhance change consumers perception and willingness to try these non-conventional edible plants. Deeper studies about people perception and attitude towards edible flowers are necessary to evaluate the influence of eating and shopping habits, neophobic behavior and others on their consumption.